Muscle and tendon injuries in children and adolescents [Cocukluk ve ergenlik döneminde kas ve tendon yaralanmalari.] - (:unkn) unknown (My University, 2004)
The pediatric athlete with open physeal plates is more susceptible to growth plate injuries and avulsion fractures than to ligament and muscle-tendon injuries that most often occur in adults. Muscle contusions and strains are common injuries in young athletes. Although they are rare in the early and middle stages of childhood, they become quite common during the growth spurt period. Healing of muscle tissues is much more rapid in children than that in adults, but it must be ensured that full motion and full strength are regained before returning to sports activities, because recurrences of injuries may result in more serious complications such as myositis ossificans. On the other hand, acute tendinous injuries are quite rare in children; however, repetitive submaximal stress may lead to overuse syndromes. This article reviews the basic anatomy and function of skeletal muscle and discusses the physiopathology of muscle-tendon injuries, and the methods of treatment and prevention, with particular focus on the growing child.